2001
DOI: 10.1046/j.1440-1819.2001.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual event‐related potential in mild dementia of the Alzheimer's type

Abstract: Visual event-related potentials (ERP) and behavioral measures were recorded during a geometrical-figure discrimination task to examine sensory processing in 10 patients with mild dementia of the Alzheimer's type (DAT) and 10 age-matched controls. No difference existed between the groups in P1, N1, and P2 potentials, which reflects the early stage of sensory processing, as well as in NA potential, which reflects pattern recognition. The patients showed reduced amplitude of P3 potential, retarded reaction time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 31 publications
6
25
0
Order By: Relevance
“…However, the majority of studies used auditory stimuli for ERPs acquisition. Those less frequent studies that examined ERPs to visual stimuli and used classical oddball paradigm are not consistent in their findings regarding differences between patients with AD and normal controls: while Verleger et al [50] did not find any change of visual ERPs in patients with AD, Saito et al [51], Daffner et al [52] and Pokryzsko-Dragan et al [19] reported only reduced P300 amplitudes in patients with AD, and Onofri et al [53] and Everes et al [54] described only prolonged P300 latencies in patients with AD, which was also our case. Further, Polich and Hoffmann [55] found both decreased amplitudes and prolonged latencies in patients with AD.…”
Section: Visual Erpsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the majority of studies used auditory stimuli for ERPs acquisition. Those less frequent studies that examined ERPs to visual stimuli and used classical oddball paradigm are not consistent in their findings regarding differences between patients with AD and normal controls: while Verleger et al [50] did not find any change of visual ERPs in patients with AD, Saito et al [51], Daffner et al [52] and Pokryzsko-Dragan et al [19] reported only reduced P300 amplitudes in patients with AD, and Onofri et al [53] and Everes et al [54] described only prolonged P300 latencies in patients with AD, which was also our case. Further, Polich and Hoffmann [55] found both decreased amplitudes and prolonged latencies in patients with AD.…”
Section: Visual Erpsmentioning
confidence: 94%
“…Another difference among the aforementioned studies is that some of them employed mental counting task [53], while the other ones used button (joystick) pressing task [50][51][52]. According to Polich and Corey-Bloom [20], it is more recommendable to perform the pressing tasks since it gives more reliable results.…”
Section: Visual Erpsmentioning
confidence: 99%
“…In this paper we will focus on the P3 component, a well studied component of the ERP that is related to high-level attention-dependent cognitive processing [16][17][18]. Reductions of the P3 component are not uncommon in psychiatric and neurological disorders with cognitive dysfunction like ADHD [19], schizophrenia [20] and dementia [21].…”
Section: Introductionmentioning
confidence: 99%
“…These ‘non‐target visual P3s’ may occur when no task is demanded 10 . Non‐target visual P3s may occur, with decreased amplitudes, in patients with dementia of Alzheimer type 11 …”
Section: Introductionmentioning
confidence: 99%